Aquatic macrophytes papermaking using Western method - Abdul Aziz, Nur Aznadia (2012)
This study was carried out to determine the suitable aquatic macrohpytes for papermaking based on the examination of its fiber dimensions, chemical compositions and suitable material for paper colouring purposes. Nine species of aquatic macrophytes, Cyperus digitatus, Cyperus halpan, Cyperus sp., Eichhornia crassipes, Eleocharis dulcis, Nelumbo nucifera, Alisma plantago-aquatica, Scirpus grossus, and Typha angustifolia were used in fiber dimensions. Whereas, three species, Cyperus sp., Scirpus grossus and Typha angustifolia used for cellulose determination. Species were collected from wetland area around UPM and Meru, Selangor. Tumeric was used as natural dye and mural colour was used as artificial dye for paper colouring purpose. Scirpus grossus (stems and leaves) and N. nucifera (blades) were the most suitable aquatic plants for pulp and papermaking based on its fiber dimensions. Its slenderness ratio was more than 60, flexibility coefficient in the range of wood fiber 55-70 and Runkel ratio less than 1. Based on chemical compositions between three species, T. angustifolia shows the most suitable for papermaking due to its high cellulose (44.05 ± 0.49%) and hemicellulose (54.84 ± 4.27%) contents. The most high quality paper produced based on paper strength and quality was Cyperus sp. due to its high tensile strength (1.69 ± 0.18 kN/m), high breaking length (731.68 ± 72.75 m) and low moisture content (9.54 ± 1.08%). Paper produced using natural dye (turmeric) was more attractive compared to paper coloured by artificial dye due to the aesthetical value of the paper.